Intensify Biodegradation Process Of Polylactic Acid (pla) Waste Generated From 3d Printing Activities - MUHAMMAD Naqib Hamdan; AMIR Mustaqim Mohd Naim; NURADLYNA Safyah Mohd Rozi; MOHD Shaiful Sajab; Ts. Dr. Hatika Kaco (Trans Tech Publications Ltd, Switzerland, 2024)
Materials Science Forum, Volume 1114, Page (137–144) This is a preprint article, it offers immediate access but has not been peer reviewed.